The Strategic Role of Cyber Intelligence in Identifying Cyber Threats: An Empirical Study of Mustang Panda in South East Asia and Indonesia - ., Krisnayanto; ., Suryadi (Journal of Ecohumanism, 2025)
The cyber espionage threat posed by the Mustang Panda group has become a critical concern in cybersecurity, particularly within the Southeast Asian region. This group targets strategic sectors in Indonesia, creating significant risks to national security. This study aims to examine the strategic role of intelligence in detecting and addressing these threats through an approach grounded in empirical data. By integrating data from cybersecurity reports and metadata analysis, the research identifies the operational patterns and modus operandi of the Mustang Panda group in Southeast metadata analysis and the operational patterns and modus operandi of the Mustang Panda group in Southeast Asia. Additionally, it addresses gaps in the existing literature, which predominantly focuses on technical aspects, by offering theoretical insights and practical contributions to developing both theoretical insights and practical contributions to the development of intelligence strategies. The findings reveal that a structured, evidence-based intelligence approach can significantly enhance the effectiveness of detecting and mitigating cyber espionage threats. Furthermore, the study provides a strategic framework to strengthen Indonesia’s and South East Asia's Asia cyber intelligence capabilities and offers policy recommendations relevant to decision-makers. This research addresses a critical gap in the cybersecurity literature and makes a tangible contribution to managing increasingly complex cyber threats in the digital era.